2022
DOI: 10.3390/atmos13040583
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Health Risk Assessment of Mercury Exposure via Indoor and Outdoor Household Dust in Three Iranian Cities

Abstract: This study aims to increase our current knowledge on the concentration of particulate-bound mercury (PBM) in urban environments of three Iranian cities, where high concentrations of dust particles can act as carriers for mercury transport and deposition. A total of 172 dust samples were collected from Ahvaz, Asaluyeh, and Zabol residential houses and in outdoor air and were analyzed for total mercury content. Ahvaz is a highly industrialized city with large metallurgical plants, refineries, and major oil-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 113 publications
1
11
0
Order By: Relevance
“…Abliz et al [ 134 ] reported that the main sources of Hg pollution are coal combustion industries and coal gangue dumps. The level of Hg in the environment has increased primarily as a result of industrialization and its byproducts [ 67 , 135 ]. With the second-largest gas reserves in the world, Asaluyeh has the largest oil and gas reserves in Iran.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abliz et al [ 134 ] reported that the main sources of Hg pollution are coal combustion industries and coal gangue dumps. The level of Hg in the environment has increased primarily as a result of industrialization and its byproducts [ 67 , 135 ]. With the second-largest gas reserves in the world, Asaluyeh has the largest oil and gas reserves in Iran.…”
Section: Resultsmentioning
confidence: 99%
“…Another large oasis city in Iran (Ahvaz) has a high contamination of HMs in surface dust, with Hg, Pb, Mn, V, and Cr exhibiting higher health risks to residents of both residential and industrial areas [ 66 ]. The concentration of particulate-bound Hg in the USD of different oasis cities (Ahvaz, Asaluyeh, and Zabol) is associated with industrial development and oil- and gas-related activities [ 67 ]. In addition, children pose a considerable non-carcinogenic health risk to their bodies through the inhalation of indoor dust in Ahvaz.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has also demonstrated a correlation between residential atmospheric heavy metal concentrations and urinary mercury concentrations in Korean adults, suggesting that urinary mercury levels could be an alternative indicator for atmospheric mercury exposure [ 25 ]. The dynamics of outdoor air can introduce airborne mercury to indoor environments, influencing indoor air quality and, subsequently, house dust heavy metal concentrations [ 26 , 27 ]. Young children are particularly vulnerable to mercury exposure from house dust due to their frequent hand-to-mouth and object-to-mouth behaviors, proximity to the ground, and tendency to spend more time on the floor [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other potential indoor sources include building materials (furniture, paint, and fluorescent lamps), appliances, and electronics, including LCD displays, monitors, batteries, clothes dryers, irons, washing machines, fluorescent bulbs, neon lights, and thermometers. (Dahmardeh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%